Negative pressure wound therapy—two novel approaches to healing dehisced vascular bypass wounds. (2nd June 2021) - O'Malley, Paula; McDonnell, Ciaran
Abstract : The use of negative pressure wound therapy (NPWT) in surgical wound healing by secondary intention is well known. Its use in healing dehisced vascular bypass wounds is contraindicated by manufacturers due to exposed vasculature and risk of bleeding. There is an increasing body of knowledge to support the use of NPWT in vascular wounds in order to prevent graft excision and the need for flap closure. This paper reports the use of two different approaches using NPWT to heal dehisced, infected vascular groin bypass wounds in two patients. Both patients had lower limb bypass using Dacron (Vascutek Ltd., UK) grafts and subsequently became infected, dehisced and required debridement. Following debridement, graft was visible in the wound bed and NPWT was applied to facilitate healing. Case one had polyurethane (black) foam and a layer of petroleum-impregnated cellulose acetate mesh to prevent adherence to the graft. Case two had polyvinyl alcohol (white) (PVA) foam applied to the wound. The PVA foam was used in Case two due to pain at dressing changes. Negative pressure was initially –25mmHg but increased gradually to –125mmHg and –150mmHg, respectively, the therapeutic pressure for the respective foams. Dressings were changed every 48–72 hours and infection treated with antibiotics as appropriate. After eight days and 28 days of NPWT, respectively, graft was no longer visible. No significant bleeding was noted. These two case studies would suggest that, with precautions taken to protect the vasculature, the use of NPWT in healing dehisced vascular groin wounds is an appropriate treatment.